Home Respiratory Polygraphy to Detect Obstructive Sleep Apnea Syndrome after Supracricoid Partial Laryngectomy - Rosa Hernández-Sandemetrio; Natsuki Oishi; Tomás Chavero; Rafael Navarro; Isabel López; Enrique Zapater (International Archives of Otorhinolaryngology)
Introduction Supracricoid partial laryngectomy is a surgical treatment for advanced laryngeal cancer which is implemented to preserve organ function, but it may cause obstructive sleep apnea syndrome (OSAS) due to anatomical changes after surgery that may be neglected by clinicians.